The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1002/rcm.4490
|View full text |Cite
|
Sign up to set email alerts
|

Electrospray ionization mass spectrometric analysis of newly synthesized α,β‐unsaturated γ‐lactones fused to sugars

Abstract: Knowledge of the fragmentation mechanisms of lactones and their behaviour under electrospray ionization (ESI) conditions can be extended to larger and more complex natural products that contain an alpha,beta-unsaturated gamma-lactone moiety in their structure. Moreover, little is known about the gas-phase behaviour of alpha,beta-unsaturated gamma-lactones linked or fused to sugars. Therefore, five alpha,beta-unsaturated gamma-lactones (butenolides) fused to a pyranose ring, recently synthesized compounds with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 69 publications
(93 reference statements)
1
5
0
Order By: Relevance
“…Semi‐empirical calculations were performed to support the proposed fragmentation mechanisms. These computational methodologies have been used successfully in a wide variety of MS studies, including the fragmentation under electrospray ionization (ESI) conditions of flavonoids19, 29–32 and α,β‐unsaturated γ‐lactones fused to furanose rings,33 the fragmentation under electron ionization (EI) conditions of buspirone,34 complexation studies,35, 36 the evaluation of the strength of non‐covalent interactions37 and the study of fullerene derivatives 38…”
mentioning
confidence: 99%
“…Semi‐empirical calculations were performed to support the proposed fragmentation mechanisms. These computational methodologies have been used successfully in a wide variety of MS studies, including the fragmentation under electrospray ionization (ESI) conditions of flavonoids19, 29–32 and α,β‐unsaturated γ‐lactones fused to furanose rings,33 the fragmentation under electron ionization (EI) conditions of buspirone,34 complexation studies,35, 36 the evaluation of the strength of non‐covalent interactions37 and the study of fullerene derivatives 38…”
mentioning
confidence: 99%
“…In this study (Madeira, Rosa et al 2010) we came across an interesting behaviour of two of the compounds studied (structures depicted in Fig. 13), that are isomers.…”
Section: Gas-phase Behaviour Of -Unsaturated -Lactones Fused To Sugarsmentioning
confidence: 96%
“…We will present some examples of the application of tandem mass spectrometry together with collision induced dissociation to study the gas-phase behaviour of some aniline derivatives (Madeira 2010), , -unsaturated -lactones fused to sugars (Madeira, Rosa et al 2010) and isoflavone aglycones. (Madeira, Borges et al)…”
Section: Structure Elucidationmentioning
confidence: 99%
“…[20 -23] The fragmentation pathways of five-membered ring lactones using electrospray ionization mass spectrometry have already been reported. [19,24] Recently we reported the gas-phase behaviour of α,β-unsaturated γ -lactones fused to pyranose rings, [25] nevertheless, studies on the gas-phase behaviour of monosaccharide derivatives of this type are still lacking. In fact, studies that deal with the gas-phase behaviour of monosaccharides are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…These inexpensive computational methodologies have been successfully employed in mass spectrometry studies, for example in the fragmentation of flavonoids and flavonoid diglycosides [31,32] and, more recently, α,β-unsaturated γ -lactones fused to pyranose units. [25] Furthermore, semi-empirical calculations were used in complexation studies, [33,34] in the evaluation of the strength of non-covalent interactions, [35] establishment of fragmentation pathways under EI conditions [36] and in the study of fullerene derivatives. [37] The fragmentation pathways are greatly influenced by the type of precursor ion, and several studies have shown that protonated species fragment more readily than metalcationized ones since the metal cationization alters the stability of the product ions.…”
Section: Introductionmentioning
confidence: 99%